2010
DOI: 10.1074/jbc.m109.046425
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Nogo Receptor Down-regulates Expression of Neuronal Nogo-A to Enhance Axonal Regeneration

Abstract: Nogo-A, a member of the reticulon family, is present in neurons and oligodendrocytes. Nogo-A in central nervous system (CNS) myelin prevents axonal regeneration through interaction with Nogo receptor 1, but the function of Nogo-A in neurons is less known. We found that after axonal injury, Nogo-A is increased in dorsal root ganglion (DRG) neurons unable to regenerate following a dorsal root injury or a sciatic nerve ligation-cut injury and that exposure in vitro to CNS myelin dramatically enhanced neuronal Nog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 64 publications
0
33
2
Order By: Relevance
“…However, at least some of the reported effects of NgR1(310)-Fc may be an artifact of axon labeling methods (Steward et al 2007). In an independent study, NgR1(310)-Fc was reported to stimulate regrowth of myelinated sensory axons into the dorsal root entry zone, spinal cord white and grey matter following dorsal root crush injury (Harvey et al 2009;Peng et al 2009). …”
Section: Mechanisms Of Myelin-associated Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least some of the reported effects of NgR1(310)-Fc may be an artifact of axon labeling methods (Steward et al 2007). In an independent study, NgR1(310)-Fc was reported to stimulate regrowth of myelinated sensory axons into the dorsal root entry zone, spinal cord white and grey matter following dorsal root crush injury (Harvey et al 2009;Peng et al 2009). …”
Section: Mechanisms Of Myelin-associated Growth Inhibitionmentioning
confidence: 99%
“…NgR1(310)-Fc complexes with NgR1 ligands and competes for ligand binding to neuronal cell surface receptors, including NgR1. In vitro, NgR1(310)-Fc overcomes CNS myelin inhibition and promotes neurite outgrowth of different types of neurons plated on substrate bound CNS myelin or individual inhibitors (Fournier et al 2002;He et al 2003;Zheng et al 2005;Peng et al 2009). Interpretation of in vivo effects of NgR1(310)-Fc administration is more complicated: intrathecally administrated NgR1(310)-Fc was reported to increase growth of corticospinal and raphaespinal axons and to improve functional outcome after spinal cord injury (Li et al 2004;Wang et al 2006).…”
Section: Mechanisms Of Myelin-associated Growth Inhibitionmentioning
confidence: 99%
“…AAV/sNgR has been used to infect retinal ganglion cells to enhance the regeneration of the optic nerve [51]. Peng et al transduced DRG neurons with sNgR via subcutaneous inoculation of HSV vector and they found that the expression of sNgR in DRG neurons improved regeneration of myelinated fibres in both dorsal root and spinal DREZ following dorsal root crush [52]. Recovery of proprioception was significantly improved in the HSV/sNgR injected animals.…”
Section: Soluble Nogo Receptormentioning
confidence: 96%
“…Subsequent recombinant virus screening and purification were conducted using the methods as described previously. 31 The identities of the recombinant viruses were confirmed by PCR amplification of the transgenes followed by DNA sequencing. The EPO and the control GFP vectors were also confirmed by induced expression of EPO or GFP in Vero cells by DOX.…”
Section: Construction Of Regulatable Epo and Gfp Expression Vectorsmentioning
confidence: 99%
“…The regulatable gene expression unit in plasmids pSASB3-EPO-HA and pSASB3-GFP-HA was flanked by sequences corresponding to the up-and downstream sequences of the ICP4 open reading frame in HSV-1 at the 5′-and 3′-ends, respectively, which serve as the basis for homologous recombination between the plasmid DNA and the viral genome. 31 To generate the HSV-1-based recombinant vector, 3.5 × 10 5 7b cells in Pstrep-free Dulbecco's modified Eagle's essential medium were seeded into 6-well plates and incubated at 37 °C in an atmosphere of 5% CO 2 overnight. Cells were infected with UL42E1G6 at multiplicities of 3, 1, 0.5, and 0.1 plaque-forming units per cell, followed 1 hour later by transfection with 2 μg of pSASA3-EPO-HA or pSASB3-GFP-HA.…”
Section: Construction Of Regulatable Epo and Gfp Expression Vectorsmentioning
confidence: 99%